International market entry mode – a systematic literature review. (3rd October 2018) - Schellenberg, Michael; Harker, Michael John; Jafari, Aliakbar
Abstract: This wholly conceptual paper examines the breadth of literature on Market Entry Modes, a fundamentally important and strategic issue for managers in growing organisations of all sizes in all sectors. Key concepts and terms are defined and then a set of key Internationalisation Theories are systematically and critically reviewed, these being: the Transaction Cost Approach, Institutional Theory, the Eclectic Paradigm, the Uppsala Internationalisation Model and the Resource Based View. The final portion of the paper is integrative and highlights three key literature gaps as signposts for future work.